Double C–H amination by consecutive SET oxidations. Issue 44 (12th May 2016) - Evoniuk, Christopher J.; Hill, Sean P.; Hanson, Kenneth; Alabugin, Igor V.
Abstract : A new method for intramolecular C–H oxidative amination is based on a FeCl3 -mediated oxidative reaction of anilines with activated sp 3 C–H bonds. Abstract : A new method for intramolecular C–H oxidative amination is based on a FeCl3 -mediated oxidative reaction of anilines with activated sp 3 C–H bonds. The amino group plays multiple roles in the reaction cascade: (1) as the activating group in single-electron-transfer (SET) oxidation process, (2) as a directing group in benzylic/allylic C–H activation at a remote position, and (3) internal nucleophile trapping reactive intermediates formed from the C–H activation steps. These multielectron oxidation reactions proceed with catalytic amounts of Fe(iii ) and inexpensive reagents.